Preferential accumulation of small (<300 μm) microplastics in the sediments of a coastal plain river network in eastern China. (1st November 2018) - Wang, Zhenfeng; Su, Bobo; Xu, Xiaoqun; Di, Di; Huang, Hong; Mei, Kun; Dahlgren, Randy A.; Zhang, Minghua; Shang, Xu
Abstract: Microplastics are a global concern for their threat to marine ecosystems. Recent studies report a lack of smaller microplastics (<300 μm) in oceans attributed to a "loss in ocean". Several hypotheses have been proposed to explain the absence of smaller microplastics, but their fate and transport remain an enigma. Our study recovered high concentrations of microplastics (32947 ± 15342 items kg −1 dry sediment) from sediments of a coastal plain river network in eastern China, with the <300 μm fraction accounting for ∼85% of total microplastic particles. Microplastic concentrations were generally higher in sediments from tributary streams and streams surrounded by industrial land use. The high variability of microplastics within the watershed indicates that the distribution of microplastics is regulated by several factors, such as distance to source(s), river flow characteristics, buoyancy behavior, degradation, etc. Fragment and foam forms dominated the small microplastics, while fibers were less prevalent in the <300 μm fraction and more abundant in downstream sites. The dominance of small microplastics in riverine sediments in this study provides a possible mechanism to explain the relative absence of small microplastics in the ocean, and advocates for quantification of the whole size spectrum of microplastics in future studies of riverine microplastic fluxes. Graphical abstract: Image 1 Highlights: Lots of microplastics are recovered from the sediments of a plain river network. Small (<300 μm) fraction (SMPs) dominated (∼85%) microplastics in the sediments. Distribution patterns varied from different morpholocical types of microplastics. Accumulation in freshwater sediments may contribute to the loss of SMPs in ocean. Nile Red staining is a promising methods for quantifying abundant SMPs.